2005
DOI: 10.1093/eurheartj/ehi481
|View full text |Cite
|
Sign up to set email alerts
|

Peripartum cardiomyopathy: inflammatory markers as predictors of outcome in 100 prospectively studied patients

Abstract: Plasma markers of inflammation were significantly elevated and correlated with increased LV dimensions and lower LVEF at presentation. Baseline Fas/Apo-1 and higher NYHA FC were the only predictors of mortality. Normalization of LVEF was only observed in 23% of this African cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
231
4
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(259 citation statements)
references
References 27 publications
15
231
4
9
Order By: Relevance
“…This is in keeping with previous reports in Kano and Sokoto [30] [31] [32]. Patients from Zaria, South Africa and Haiti were however older than our patients with the mean age of the South African and Haiti patients being 31.6 ± 6.6 years and 31.8 ± 8.1 years respectively [33] [34]. This therefore explains the relatively larger number of primipara in our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in keeping with previous reports in Kano and Sokoto [30] [31] [32]. Patients from Zaria, South Africa and Haiti were however older than our patients with the mean age of the South African and Haiti patients being 31.6 ± 6.6 years and 31.8 ± 8.1 years respectively [33] [34]. This therefore explains the relatively larger number of primipara in our study.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence is however lower in other parts of the world. In South Africa, it was reported to be 1:1000 live births, while in Haiti it was found to be 1:300 live births [33] [34].…”
Section: Discussionmentioning
confidence: 99%
“…4 Interestingly, the results of Xia et al showed that, despite the theory that PPCM is caused by an anomalous inflammatory response, the levels of high-sensitivity CRP, a biomarker characterizing inflammation status, did not present any significant difference between the 2 groups.…”
Section: To the Editormentioning
confidence: 94%
“…Nevertheless, in the study of the small number of Haitian PPCM patients, there was no statistically significant difference in CRP plasma levels in survivors versus deceased patients. 8 Therefore, the issue is further supported by a study on the level of serum CRP in patients with PPCM.…”
Section: To the Editormentioning
confidence: 98%